Kompensasi, Beban Kerja dan Lingkungan Kerja terhadap Turnover Intention (Studi pada Kurir Ekspedisi Anteraja Cabang Yogyakarta) - Muhammad Naufal Muzakki; Kusuma Chandra Kirana; E. Didik Subiyanto (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine and test the influence of compensation, workload and work environment on turnover intention among Anteraja couriers, Yogyakarta branch. Sampling used random sampling technique and a sample of 57 couriers was obtained. Data collection uses questionnaires. The data analysis technique used in this research is multiple linear regression analysis. The research results show that compensation and work environment have no effect on turnover intention, while workload has a positive effect on turnover intention. Conclusion: Compensation and work environment do not have a significant influence on the intention to change jobs (turnover intention) for Anteraja couriers, Yogyakarta branch. Workload has a significant positive influence on the intention to change jobs (turnover intention) for Anteraja couriers, Yogyakarta branch. Keywords: Workload, Compensation, Work Environment, Turnover Intention